Podcasts as a platform for sharing and disseminating experiences and expertise between young adults with cancer and radiotherapy researchers - Lisa Whittaker; Elena Espinosa-Cabrera; Helen Haar; Elly Hall; Sophie Lambert; Jesse Tristram; Michaela Vladykova; Rebecca Drake; Gemma Eminowicz; Patrycja Lewandowska; Catarina Veiga; Amanda Webster; et al. (Research Involvement and Engagement)
Abstract We set out to co-create a collaborative project that would raise awareness of radiotherapy, explore young adults’ experiences of cancer treatment, and share radiotherapy research with audiences beyond academia. To do this, we partnered radiotherapy researchers with young adults who had undergone radiotherapy, co-creating a series of episodes for an established oncology podcast. These conversations offered space for participants to share their stories and personal insights, both as patients and as researchers. Six young adults and six researchers took part, supported by preparatory discussions to help shape meaningful conversations. Each podcast episode featured unique patient experiences alongside different areas of radiotherapy research. An independent evaluation, based on semi-structured interviews with participants and hosts, highlighted the importance of relational connection, mutual respect, and the value of having a dedicated project coordinator. The episodes were downloaded over 3000 times in 120 countries. Participants described feeling heard and appreciated, and several researchers reflected on the renewed motivation and perspective gained through the project. This collaboration suggests how podcasting has the potential to serve as an accessible and emotionally resonant tool for engagement, enabling researchers and patients to connect in new ways and share knowledge with a broader public. Future projects of this kind may benefit from a similar co-creative and well-supported approach.